Hematological Profiles of HIV-infected Adults Initiating Highly Active Antiretroviral Therapy (HAART) in Uganda - Kyeyune, Rachel; Saathoff, Elmar; Ezeamama, Amara; Fawzi, Wafaie; Loescher, Thomas; Guwatudde, David (AIDS Research and Human Retroviruses, 2014)
Cytopenias are the most common HIV-associated hematological abnormality. Cytopenias become more prevalent as HIV progresses and are often fatal. Sex, race, geographical location and comorbidities such as tuberculosis have been associated with cytopenias. Data from resource-limited settings about the prevalence, correlates and trends in cytopenia are limited. This analysis assessed the prevalence and correlates of cytopenia at initiation of HAART and the trend in cytopenias among HAART-treated AIDS patients in Uganda.
Keywords: Uganda; Hematological Profiles; HIV-infected Adults; Highly Active Antiretroviral Therapy (HAART)